Negative temperature coefficient effect of TPU/SWCNT/PEDOT:PSS polymer matrices for wearable temperature sensors - Yeongu Choi; Minhyeok Kim; Hongyun So (Polymer Testing)
Composite-based temperature sensors utilizing the negative temperature coefficient (NTC) effect have gained significant attention across various fields, particularly in healthcare. However, the development of innovative, highly linear, and high-performance NTC-based temperature sensors remains a challenge. In this study, we developed a composite temperature sensor comprising thermoplastic polyurethane (TPU), single-walled carbon nanotubes (SWCNTs), and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS). A series of performance tests demonstrated that the TPU/SWCNT/PEDOT:PSS (TSP) composite effectively monitors temperature variations with both linearity and superior performance, attributed to the synergistic NTC effects of SWCNTs and PEDOT:PSS. This flexible temperature sensor retained its sensing functionality after repeated cycles of temperature fluctuations and multiple bending tests. Moreover, due to the unique properties of CNTs, the TSP sensor exhibited photothermal responses, showing highly sensitive resistance changes upon exposure to infrared radiation. The TSP sensor proved to be effective for various practical applications, including biosignal monitoring through thermal detection, temperature tracking during phone charging, and accurate temperature sensing on curved surfaces. Additionally, non-contact heat detection can be reliably performed regardless of whether tensile stress is applied. These findings underscore the immense potential of TSP sensors for future use in wearable healthcare technologies.